(3GdESaGQ Yf Mce GdCSaGQs - (3eXaQ GdOjf eMehO GdYfJCHj GdGeTGWjs ((3eUQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ HGdCSaGQ , ddJacQ hGdEYJHGQ s
(3BNQgG (B:s
,(3GeG eG jMJGL Edjg ef GdSfhfGJ hSfhf jTQ GddKI hGdCSfGf , bQf Cjd eMQb hgPG BNQ eG CQOfGg hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B100 - (3U(B110s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3hgj QSGdI ai HjGf GdeGLI Edi GdSaQ heG jfHZi ddeSGaQ aYdg s
(3hGdSaQ ai GdMQ hGdTJGA hMaX GdCWQGa hGddhf hCehQ GdejGg hGdSaQ ai GdHMQ s
(3heG jUMHg GdeSGaQ ef GdCOhjI GdeaQOI hGdeQcHI s
(3bQf GdfSN (B:s
Keywords: (3GdWHs